The relationship between future time perspective, self-efficacy and risky sexual behaviour in the Black youth of central South Africa. (3rd March 2016) - Abousselam, Nikki; Naudé, Luzelle; Lens, Willy; Esterhuyse, Karel
Abstract: Background : An interest exists in understanding why adolescents partake in risky sexual behaviours, as well as the risk and protective practices associated with risky sexual behaviour. Aim : The aim of this study was to investigate the moderator effect of future time perspective in the relationship between self-efficacy and risky sexual behaviour. Methods : A random cluster consisting of 467 learners from English medium high schools of central South Africa participated in this study. The participants' risky sexual behaviour, self-efficacy and future time perspective were measured with the Perceptions of HIV/AIDS Risk Survey, Generalised Perceived Self-efficacy Scale and the Zimbardo Time Perspective Inventory, respectively. Product term regression analysis was performed. Results : It was found that both self-efficacy and future time perspective were negatively related to risky sexual behaviour. No moderating effect was found for future time perspective in the relationship between self-efficacy and risky sexual behaviour. Conclusions : Self-efficacy and future time perspective were identified as qualities that protect adolescents from engaging in risky sexual behaviours. This finding can be useful in developing prevention programmes. Intervention programmes aimed at the youth should foster a sense of hope and possibility about the future and the development of goals and aspirations to prevent risky behaviour.